REFLEKSI PROFIL PELAJAR PANCASILA DALAM KISAH RAMĀYĀNA SEBAGAI PEMBENTUK PELAJAR HINDU UNGGUL DAN MULIA - Made Mardika; Ni Komang Sutriyanti; I Dewa Gede Darma Permana (Padma Sari: Jurnal Ilmu Pendidikan, 2023)
In order to bridge the development of student competencies in a global level, the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia proposed the Pancasila Student Profile as a guideline in shaping the nation's quality generation based on the noble values of Pancasila. But even so, there is no clear reflexion for Hindu students in practicing the six dimensions given by the Pancasila Student Profile. For this reason, researchers in this case are interested in exploring the reflection of the dimensions of the Pancasila Student Profile in the Ramāyāna story. This research formulates several problem formulations, namely related to the nature of the Ramāyāna story, the essence of the Pancasila Student Profile, and the reflection of the Pancasila Student Profile in the Ramāyāna story. Through the type of qualitative research with a literature study approach, as well as processing the data obtained using data analysis from Miles and Huberman, the results of this study indicate that, there are several reflections on the dimensions of the Pancasila Student Profile in the story of Ramāyāna. Where the reflection is taken through several fragments of the story or the actions of the characters in the Ramāyāna story that can be used as guidelines by Hindu students as superior and noble individuals.